DAMPAK EKONOMI DAN LINGKUNGAN PERTAMBANGAN EMAS TANPA IZIN (PETI) DI DESA DEMANG KECAMATAN LIMUN KABUPATEN SAROLANGUN (Jurnal Riset Manajemen dan Akuntansi, 2023)
Community mining activities are a category of small-scale mining, which is traditionally cultivated. This gold mining is carried out illegally, it is said to be illegal not only because it is done without a permit, but in practice mining is carried out without rules so that it can damage the environment. Gold mining or often called dompeng is no stranger to teh community, it has even become a normal work activity for the community/people doing it. This study aims to find out how the impact and socio-economic conditions of the community on gold mining. This study uses qualitative methods, the data in this study were obtained from primary data and secondary date. Using the method of observation, interviews and documentation. The information in this study is the owner of the mine, miners, farmers, community leaders and village officials. From the results of the study it can be concluded that gold mining activities without a permit have both positive and negative impacts on ecological, economic and social aspects. The negative impact on the environment is environmental changes caused by gold mining activities which make the area around the mining area polluted, such as muddy river water. While the positive impact is the economic conditions of the Demang Village Community after switching to mining workers and gold mining enterpreneurs, increasing income and meeting the needs of the community. As well as the very limited and uneven economic conditions of the community, this is a factor causing the rise of gold mining.